Attributes influencing food products enhancement / Mohd Zahir Zainol - Zainol, Mohd Zahir (2013)
This research aims to investigate the relationship among the attributes that influencing food product enhancement. The initial ideas is to study the attributes that is sosio culture, consumer value, market positioning strategy towards product enhancement. This research was conducted on a consumer in state of Melaka. Three hundred selected consumer were participated in this research. The finding reveal that there is a positive relationship between the three all determinant variables.Socio culture, market positioning and consumer value are agreed to be the most influential attributes in food product enhancement.